PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENINGKATKAN LITERASI KEUANGAN SYARIAH DALAM MELINDUNGI MASYARAKAT DARI PINJAMAN ONLINE ILLEGAL - Bangun Adhi Wasito; Muhammad Tho’in; Abdul Haris Romdhoni (ITB AAS INDONESIA Surakarta, 2025)
This research aims to investigate and analyze the role of Islamic financial institutions in enhancing community financial literacy; identify the strategies of Islamic financial institutions in protecting the community from illegal online loans, and evaluate the challenges faced by Islamic financial institutions in increasing financial literacy and protecting the community from illegal online loans. This research method uses a descriptive qualitative approach. The data sources used are secondary data such as references, journals, books, or documentation data related to the research. Data collection techniques include literature study. The data analysis technique used is qualitative analysis with a literature study conducted through several stages, including formulating research questions, searching for literature sources, and evaluating literature sources. The research results show that Islamic Financial Institutions (LKS), especially BMT and Islamic cooperatives, play an important role in increasing Islamic financial literacy through product education, providing products according to needs, community economic empowerment, financial inclusion, and collaboration. LKS needs to implement proactive strategies to protect the community from illegal online loans, including education, providing alternative Islamic financing, collaborating with OJK, increasing Islamic financial literacy, and community economic empowerment. LKS faces challenges in increasing financial literacy and protecting the community from illegal online loans, such as lack of public understanding, limited access to information, and competition with conventional financial institutions. To overcome these challenges, LKS needs to increase education, expand service reach, improve HR quality, strengthen collaboration, develop innovative products, and utilize digital technology. With comprehensive efforts, LKS can increase community financial literacy and protect them from the dangers of illegal online loans. This research shows that financial education, both formal and informal, is effective in increasing financial literacy.